Pendekatan Tarhīb dalam Dakwah Buya Yahya: Analisis Teori Behaviorisme - Mila Rahmawati; Saskiah Rismayani; Qudratullah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This study aims to analyze the structure of threats (tahrib) in Buya Yahya's lecture entitled “Ngeri! Ancaman & Hukuman Meninggalkan Sholat Menurut Jumhur Ulama” (Terrifying! Threats & Punishments for Abandoning Prayer According to the Majority of Scholars) as a punishment stimulus in the behaviorist framework. The method used in this study is qualitative with a literature review approach. Data was obtained through Buya Yahya's sermons accessed via his official YouTube channel and other supporting literature related to the concept of tahrib, behaviorism theory, and the psychology of preaching. The results of the study show that Buya Yahya's sermons form a stimulus-response pattern in line with the principles of behaviorism, where tarhīb and punishment function as educational tools with the hope of shaping religious behavior in accordance with Islamic values